Nature of Pharmacophore Influences Active Site Specificity of Proteasome Inhibitors - Screen, Michael (American Society for Biochemistry and Molecular Biology, 2010)
Proteasomes degrade most proteins in mammalian cells and are established targets of anti-cancer drugs. The majority of proteasome inhibitors are composed of short peptides with an electrophilic functionality (pharmacophore) at the C terminus. All eukaryotic proteasomes have three types of active sites as follows: chymotrypsin-like, trypsin-like, and caspase-like. It is widely believed that active site specificity of inhibitors is determined primarily by the peptide sequence and not the pharmacophore. Here, we report that active site specificity of inhibitors can also be tuned by the chemical nature of the pharmacophore. Specifically, replacement of the epoxyketone by vinyl sulfone moieties further improves the selectivity of β5-specific inhibitors NC-005, YU-101, and PR-171 (carfilzomib). This increase in specificity is likely the basis of the decreased cytotoxicity of vinyl sulfone-based inhibitors to HeLa cells as compared with that of epoxyketone-based inhibitors.